2015
DOI: 10.1080/00218839.2016.1189231
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of a food supplement HiveAlive™ on honey bee colony strength and Nosema ceranae spore counts

Abstract: The long term effect of HiveAlive™, a commercial food supplement, was evaluated with respect to colony population size and Nosema ceranae spore loads. The supplement was administered in sugar syrup at a dose of 2.5 ml per liter of syrup to up to 20 colonies per group for a period of 2 years. Its use before and after winter increased a colony's worker population size by 89% and reduced Nosema ceranae spores by 57% compared to control colonies. These results represent the first-known hive manipulation to have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
3
20
0
1
Order By: Relevance
“…A number of commercial supplements (HiveAlive TM , Api-Bioxal ® and ApiHerb ® , “BEEWELL AminoPlus”, Nozevit ® , BeePro ® , MegaBee ® , etc.) have been tested for anti- N. ceranae activity as well [ 64 , 65 , 66 , 67 , 68 ]. For instance, administration of HiveAlive TM and ApiHerb ® significantly reduces N. ceranae spores load [ 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of commercial supplements (HiveAlive TM , Api-Bioxal ® and ApiHerb ® , “BEEWELL AminoPlus”, Nozevit ® , BeePro ® , MegaBee ® , etc.) have been tested for anti- N. ceranae activity as well [ 64 , 65 , 66 , 67 , 68 ]. For instance, administration of HiveAlive TM and ApiHerb ® significantly reduces N. ceranae spores load [ 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…have been tested for anti- N. ceranae activity as well [ 64 , 65 , 66 , 67 , 68 ]. For instance, administration of HiveAlive TM and ApiHerb ® significantly reduces N. ceranae spores load [ 64 , 65 ]. Application of the dietary amino acid and vitamin complex called “BEEWELL AminoPlus” decreases N. ceranae spore and protects honey bees from immune suppression by upregulating the expression of genes for immune-related peptides (abaecin, apidaecin, hymenoptaecin, defensin and vitellogenin) [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation and a larger sample size is needed in order to confirm these results, as van den Heever et al (46) reported no effect of Nozevit® in cage trials. A 2-year survey of the seaweed-based supplement HiveAlive™ reported a decrease in colony spore loads and an increased hive population relative to controls following administration of two biannual treatments (64). Surprisingly, survival was not commented on in this study, notwithstanding the authors account for colony mortality in their analyses of colony strength (64).…”
Section: Extracts and Natural Supplementsmentioning
confidence: 99%
“…Observation of faecal deposits during week 1 showed that colony 2 displayed evidence of diarrhoea (black to dark brown compared with round, yellow and orange in the other colonies). Subsequently, all the colonies were treated with the digestive supplement HiveAlive™ (2.5 ml supplied in 1 litre of 55% sugar syrup) for 1 day (Charistos et al, 2016) and for the remainder of the trial there was no evidence of diarrhoea in colony 2 or in the other colonies.…”
Section: Colony Preparation Instalment and Monitoringmentioning
confidence: 99%